IMPACT OF FINANCIAL ENGINEERING INNOVATIONS ON PROFITABILITY: A CASE STUDY ON THE COMMERCIAL BANK OF IRAQ (TBI) FOR THE PERIOD (2012-2021) - Ksma Saber Awdh (Operational Research in Engineering Sciences: Theory and Applications)
The study objective was to examine the impact of financial engineering innovation on the profitability of commercial banks in Iraq (Trade Bank of Iraq). For this purpose, quantitative data was collected from the annual reports of the Trade Bank of Iraq for the period of 2012 to 2021. The data covered a total of five years before the bank approved the services for the years (2012-2016) and a period of (5) years after the adoption of the bank's new financial innovations (2017-2020) as contemporary sources of financing aimed at achieving efficiency in current financial products and developing them in a way that enhances renewable and diversified financial needs. Various profitability indicators were used namely return on assets, return on equity, earning per share, and gross income profit. The independent sample T-test results show that commercial banks' profitability in Iraq commercial bank after the adoption of financial engineering has a statistical difference. These findings contributed that there is a statistically significant effect of these innovations on the profitability of the bank for all indicators measuring the profitability of the Trade Bank of Iraq for the period before and after the use of financial innovations. The study limitations and future directions were also discussed after the conclusion of the study.